Pengaruh Pembelajaran E-Learning dan Pemberian Tugas Terstruktur Terhadap Hasil Belajar Sejarah - Sari Fatollah (Perkumpulan Kualitama Edukatika Indonesia, 2023)
This study aims to analyze the significance of the effect of e-learning and the provision of structured assignments partially and jointly on the learning outcomes of History. This research method uses correlational quantitative research with 2 independent variables and 1 dependent variable. Total population of 107 students and a sample of 33 students. The results of the research show that the instruments used are valid and reliable. The data used for data analysis has fulfilled the classical assumption test. The t test results obtained the regression equation: Y = 1.643 + 0.754 X1 + 0.259 X2 + e. The results of the t test for the e-learning learning variable show a value of t = 8.731 with a significant value of 0.000 < 0.05 while for the structured assignment variable it shows a value of t = 3.264 with a significant value of 0.003 < 0.05, which means e-learning learning and giving Partially structured assignments have a significant effect on learning outcomes History. The results of the F test for the simultaneous regression test obtained a value of F = 132.638 with a significant value of 0.000 < 0.05, which means that the effect of e-learning learning and giving structured assignments together has a significant influence on learning outcomes History. The results of the determination test (R2) obtained the value of Adjusted R Square = 0.948, which means that the influence of the independent variables on students is 94.8% while 5.2% is influenced by other variables.